2019
DOI: 10.1584/jpestics.d19-037
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure-activity relationships of new pyrazole derivatives that induce triple response in <i>Arabidopsis</i> seedlings

Abstract: Twenty-seven analogues of pyrazole derivatives were synthesized and subjected to structure-activity relationship studies on inducing the triple response in Arabidopsis seedlings. We found that 3,4-Dichloro-N-methyl-N-[(1-allyl-3,5-dimethyl-1H-pyrazol-4-yl)methyl]benzenesulfonamide (C26) exhibits potent activity on inducing the triple response in Arabidopsis seedlings. C26 (10 µM) induced an exaggerated apical hook in Arabidopsis seedlings. The curvature of the hook of the Arabidopsis seedlings was found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…We have previously shown that the modifications of the sulfonamide moiety did not significantly influence the biological activity of EH-1 . 14 ) Thus, introducing a dansyl moiety to EH-1 represents a straightforward approach to developing fluorescence-labeled EH-1 . Dansyl chloride (5-(dimethylamino)naphthalene-1-sulfonyl chloride) is a reagent that reacts with amines to produce stable blue or blue-green fluorescent sulfonamide adducts that display sufficient fluorescence properties.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that the modifications of the sulfonamide moiety did not significantly influence the biological activity of EH-1 . 14 ) Thus, introducing a dansyl moiety to EH-1 represents a straightforward approach to developing fluorescence-labeled EH-1 . Dansyl chloride (5-(dimethylamino)naphthalene-1-sulfonyl chloride) is a reagent that reacts with amines to produce stable blue or blue-green fluorescent sulfonamide adducts that display sufficient fluorescence properties.…”
Section: Resultsmentioning
confidence: 99%
“…The general procedure for preparing N -methyl- N -[(1,3,5-trimethyl-1 H -pyrazol-4-yl)methyl]-5-dimethylamino-1-naphthalenesulfonamide ( EH-DF ) was carried out by reacting N -methyl-1-(1,3,5-trimethyl-1 H -pyrazol-4-yl)methanamine with dansyl chloride in a condition as we described previously. 14 ) (yield: 33%), oil, 1 H NMR (400 MHz, CDCl 3 ); δ: 2.01 (s, 3H), 2.07 (s, 3H), 2.63 (s, 3H), 2.89 (s, 6H), 3.67 (s, 3Hs), 4.08 (s, 2H), 7.19 (d, J =7.3 Hz, 1H), 7.52–7.57 (m, 2H), 8.21 (d.d, J1=1.2, J2=7.3 Hz, 1H), 8.45 (d, J =8.6 Hz, 1H), 8.57 (d, J =8.6 Hz, 1H); 13 C NMR (100 MHz, CD 3 OD): δ 152.9, 148.2, 140.5, 135.1, 134.2 (x2), 131.4, 131.1, 130.8, 128.9, 124.2, 120.7, 116.7, 116.3, 111.5, 51.8, 45.6, 43.8, and 33.5. The HRMS-ESI calculated for C 20 H 26 N 4 O 2 S [M+H]+ was 386.1776, and we found 386.1759.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations